Medieval Franciscan approaches to the Virgin Mary: Mater Misericordiae Sanctissima et Dolorosa - McMichael, Steven J.; Shelby, Katherine Wrisley (The medieval Franciscans, 2019)
"This volume offers a sample of the many ways that medieval Franciscans wrote, represented in art, and preached about the 'model of models' of the medieval religious experience, the Virgin Mary. This is an extremely valuable collection of essays that highlight the significant role the Franciscans played in developing Mariology in the Middle Ages. Beginning with Francis, Clare, and Anthony, a number of significant theologians, spiritual writers, preachers, and artists are presented in their attempt to capture the significance and meaning of the Virgin Mary in the context of the late Middle Ages within the Franciscan movement."